Strobing of Radar Marks for Trajectory Filtration in a Body-Fixed Frame - Konstantin K. Vasiliev; Alexey V. Mattis; Oleg V. Saverkin (Известия высших учебных заведений России: Радиоэлектроника, 2019)
Introduction. Modern air targets, particularly drones, are becoming less noticeable, while their manoeuvrability continues to improve. Trajectory processing algorithms have also been improved in order to provide for effective tracking of highly manoeuvring targets. The accuracy of filtering trajectory parameters is largely determined by the reliability of radar information. This has also required an enhanced role for strobe algorithms and the need to increase the effectiveness of strobe radar marks.Aim. To develop and investigate the efficiency of a trajectory strobe algorithm based on the target motion model in a high-speed coordinate system associated with the direction of the target motion and involving the formation of a strobe in the form of a truncated elliptical sector.Materials and methods. The study considered the target motion model in the body-fixed frame. This model was taken as the basis for new trajectory filtering algorithms based on Kalman filtering. Existing methods for strobing radar marks of the target were considered and a new approach based on filtering in the body-fixed frame proposed. The new algorithm assumes the formation of a strobe in the form of a truncated elliptical sector. This form corresponds to the most probable location of the marks of the tracked target. The effectiveness of the proposed solutions is confirmed by the results of mathematical modelling carried out using MATLAB.Results. The study produced analytical expressions for the motion model, recurrent filtering and strobe algorithm in the body-fixed frame. A comparative analysis of tracking effectiveness with the same volumes of the elliptical and proposed strobes was performed. It was established that the algorithm with strobe formation in the shape of a truncated elliptical sector provides for longer target tracking up to the time of the first loss of the mark for speed and highly manoeuvring targets, when compared to the elliptical strobe algorithm. In addition, the average duration of sector strobe tracking does not in practice depend on the initial speed of the target and provides greater accuracy for small measurement error values (less than 50 m) of the coordinates than in comparison with the elliptical one. Conclusion. The described results were achieved by the ability of the strobe in the body-fixed frame to adapt to the direction of motion and target manoeuvring, allowing high-quality target tracking within a larger speed range. Such strobe formation will also reduce the likelihood of skip-ping radar marks from the tracked target and will reduce the number of false marks belonging to other trajectories inside the strobe.